2019
DOI: 10.1177/1362361319858860
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported motivations for offending by autistic sexual offenders

Abstract: Autism spectrum disorder is a neurodevelopmental disorder estimated to have elevated prevalence in forensic populations (approximately 4.5%). It has been suggested that offenders with autism spectrum disorder engage more frequently in crimes against the person and sexual offences than other types of offences such as property, driving and drug offences. To date little is empirically known about the reasons why autistic individuals engage in sexual offences, yet understanding the motivation(s) for offending are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…Future research should consider more autism-specific risk factors to try to identify differences between autistic individuals who may offend and those who may not. A mixed methods approach could offer great benefit; for example, by employing a qualitative approach to identify reasons for offending, with further objective investigation using quantitative methods (see Payne et al 2019a ). With increased knowledge and understanding of the risk factors for offending (e.g., co-occurring personality disorder or ADHD), those at high risk who have a diagnosis of autism can be provided with more tailored support with a view to preventing autistic individuals from offending.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should consider more autism-specific risk factors to try to identify differences between autistic individuals who may offend and those who may not. A mixed methods approach could offer great benefit; for example, by employing a qualitative approach to identify reasons for offending, with further objective investigation using quantitative methods (see Payne et al 2019a ). With increased knowledge and understanding of the risk factors for offending (e.g., co-occurring personality disorder or ADHD), those at high risk who have a diagnosis of autism can be provided with more tailored support with a view to preventing autistic individuals from offending.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, autistic individuals are more likely to be victimized (Gibbs & Haas, 2020; Railey et al, 2020; Salerno & Schuller, 2019; Weiss & Fardella, 2018), come into contact with criminal justice system professionals due to wandering or elopement (Copenhaver & Tewksbury, 2019) or seeking assistance (Gibbs & Haas, 2020). Research also suggests that a misunderstanding of rules and social cues (Allen et al, 2008; Payne et al, 2020), along with reduced access to services (Tint et al, 2017), and a history of abuse (Kawakami et al, 2012) may correlate with criminal justice interactions for autistic individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In a sample of adults with Asperger’s who accessed community services, Allen et al (2008) found that offending behavior was linked to obsessive interests, social naivety, and a misunderstanding of laws. Payne et al (2020) uncovered similar traits when analyzing self-reported motivations from autistic sex offenders. Copenhaver and Tewksbury (2019) further reported that a sizable number of police encounters occur because the autistic individual is wandering or missing.…”
Section: Resultsmentioning
confidence: 86%